Hygiene Sanitation and Food Bacteriology Quality of School Canteen In Elementary School In Work Areas Puskesmas II Denpasar Timur - Ni Wayan, Uripayoni (HIGIENE: Jurnal Kesehatan Lingkungan, 2020)
The school canteen is one of the school children’s snacks that has the role of realizing and determining students’ eating behavior through the provision of snacks at school. Sanitation hygiene is an effort to control food factors, people, places, and equipment that can cause illness or health problems. This study aims to determine the relationship between school canteen hygiene and sanitation with the bacteriological quality of food. This type of research is quantitative research with cross sectional design. The sample of this research is 15 elementary school canteens. The observation results of school canteen sanitation obtained 3 (20.0%) canteen with good sanitation category, 6 (40%) adequate canteen category and 6 (40%) bad canteen category. Interviews with food handlers obtained 10 people (66.7%) enough categories and 5 people (33.3%) bad categories, and laboratory tests obtained 7 samples (46.7%) qualified and 8 samples (53.3%) not eligible. Keywords: school canteen, hygiene and sanitation, bacteriological.